2010
DOI: 10.3746/jfn.2010.15.1.044
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Free Radical Scavenging Activity of Different Fractions from Hawthorn Fruit

Abstract: Hawthorn fruit is a conventional medicine used in treating cardiovascular diseases. Its therapeutic effects may relate to its antioxidant compounds. In this study, we evaluated the antioxidant activity of CH 2 Cl 2 , EtOAc, n-butanol and water fractions from 70% methanolic hawthorn fruit extract by total phenolic and flavonoid contents, total antioxidant activity, DPPH free radical scavenging activity, superoxide radical scavenging activity, reducing power assay, lipid peroxidation inhibitory activity and prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Oxidative damage appears to be related to various diseases and inflammation conditions [18,19]. Polyphenols reduce oxidative stress and provide activity associated with anti-cancer, anti-allergic, and anti-inflammatory effects [20].…”
Section: Resultsmentioning
confidence: 99%
“…Oxidative damage appears to be related to various diseases and inflammation conditions [18,19]. Polyphenols reduce oxidative stress and provide activity associated with anti-cancer, anti-allergic, and anti-inflammatory effects [20].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, a high value for total phenolic content (343.5 mg GAE/g) in the ethyl acetate extract of C. monogyna leaves was reported by Öztürk et al [12]. Park et al [13] studied the ethyl acetate fraction of hawthorn berries, which were also characterized by high phenolic and flavonoid contents (140.2 tannic mg/g and 56.5 catechin mg/g, respectively). Literature data show significant differences in total phenolic content of hawthorn, probably due to several factors such as natural habitat, genotype, growth stage, extraction procedure and method for determination of total phenolics.…”
mentioning
confidence: 93%
“…Recent reports have shown that hawthorn fruit exhibits anti-oxidant, anti-atherosclerotic, and hypolipidemic activities [ 17 - 20 ]. We previously reported on the antioxidant and anti-inflammatory properties of the methanolic extract of hawthorn fruit [ 21 , 22 ]. In this study, our objective was to investigate the mechanisms behind the anti-inflammatory activities of the water fractionated portion of hawthorn fruit on RAW 264.7 cells.…”
Section: Introductionmentioning
confidence: 99%